Flight characteristics of the summer and winter phenological form of the pine processionary moth (Thaumetopoea pityocampa) according to data from automatic pheromone traps near Asenovgrad in Bulgaria - Georgi Georgiev; Margarita Georgieva; Gergana Zaemdzhikova; Sevdalin Belilov; Maria Matova; Mihaela Hristova; Plamen Mirchev (Silva Balcanica)
The winter and summer phenological forms of the pine processionary moth (Thaumetopoea pityocampa) were recorded in two adjacent sites in the region of Asenovgrad, South Bulgaria. In the land of Muldava village (at the foot of the Rhodopes at 290 m a.s.l.), the typical winter phenological form was established, while the summer form was found in the vicinity of Dobrostan village (on the northern slopes of the Rhodopes at 1200 m a.s.l.). The calculated air fly distance between both villages is 9.3 km. In 2019, funnel automatic pheromone traps – CapTrap® were installed in Dobrostan and Muldava villages to obtain information about the flight dynamics of the male butterflies of T. pityocampa. For the studied period (June-September), hourly data on the humidity and air temperature in both sites were also analysed. In both sites, the flight started at the beginning of July and ended in the first decade of September. Two clear peaks in the flight of male butterflies were observed on 7-8 and 23-28 July, which was associated with catches of both phenological forms due to the proximity of the traps. In Dobrostan, no high maximum temperatures above 30-32 °C were measured in the days during the period July-September. In Muldava, critical temperatures for the survival of T. pityocampa were recorded in this period: July (61.3% of the days), August (87.1%) and September (23.3%).